First records of the genus Leptophion Cameron (Hymenoptera: Ichneumonidae: Ophioninae) from Vietnam - Nhi, Pham Thi; Long, Khuat Dang; Thu, Cao Thi Kim; Nga, Cao Thi Quynh; Tru, Hoang Vu; Phu, Pham Van; Hanh, Le My (Academia Journal of Biology, 2021)
The genus Leptophion is recorded for the first time from Vietnam, including new records of three species, viz. L. giganteus Shimizu & Watanabe, L. maculipennis (Cameron) and L. radiatus (Uchida), for the country. The comparative morphological and pictorial characters of Vietnamese specimens were given. In addition, variations and in-country distribution of newly recorded species were also provided.